2016
DOI: 10.1007/s40940-016-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical behaviour of SentryGlas $$^{\circledR }$$ ® ionomer and TSSA silicon bulk materials at different temperatures and strain rates under uniaxial tensile stress state

Abstract: An innovative type of connections for glass components, called laminated connections, has been developed in the last years. Two materials have been used for laminated connections: the transparent ionomer SentryGlas (SG) from Kuraray (former Dupont) and the Transparent Structural Silicon Adhesive (TSSA) from Dow Corning. In this paper, the mechanical behaviour of SG and TSSA bulk materials is studied under uniaxial tensile stress condition. The effects of strain rate and temperature variations are investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 17 publications
3
37
0
2
Order By: Relevance
“…Several authors have investigated the mechanical response of SG-laminated components [27]- [36] and the SG-bulk material [37]- [44]. Conversely, studies on the resistance of SG laminated connections are rather limited.…”
Section: Literature On Ionomer Sentryglas® (Sg) and Sg Connectionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several authors have investigated the mechanical response of SG-laminated components [27]- [36] and the SG-bulk material [37]- [44]. Conversely, studies on the resistance of SG laminated connections are rather limited.…”
Section: Literature On Ionomer Sentryglas® (Sg) and Sg Connectionsmentioning
confidence: 99%
“…The results showed that SG connections exhibit one of the largest load carrying capacity, often limited by glass failure. Limited results are available in literature at different temperatures [16], [44], [49]- [52]. Preliminary results show that temperature has a dominant effect on the mechanical response of the connection, with a severe reduction of the maximum load-carrying capacity at high temperature.…”
Section: Literature On Ionomer Sentryglas® (Sg) and Sg Connectionsmentioning
confidence: 99%
See 3 more Smart Citations